Effect of cellulase and lactic acid bacteria on the fermentation quality, carbohydrate conversion, and microbial community of ensiling oat with different moisture contents - Xu, Jinyi; Zhang, Keyi; Lin, Yufan; Li, Mengxin; Wang, Xuekai; Yu, Qiang; Sun, Hong; Cheng, Qiming; Xie, Yixiao; Wang, Chunmei; Li, Ping; Chen, Chao; et al. (Frontiers in Microbiology, 2022)
Oat (Avena sativa L.) is one of the most widely cultivated crops used as forage. The aim of this study was to evaluate the effects of cellulase and Lactobacillus plantarum interactions with different moisture contents on oat ensiling. Oats with three moisture contents were treated with nothing (C), cellulase (CE), lactic acid bacteria (LP), or CE+LP and ensiled for 30 d and 60 d. Compared with the control, LP and CE treatments increased crude protein and lactic acid concentrations and reduced the pH and ammonia nitrogen/total nitrogen (NH3-N/TN) ratios of silages. The addition of CE improved lignocellulosic degradation, compared with approximately 67% (LD) and 81% moisture content (HD) ensiling, CE (CE, CE+LP) ensiling in the approximately 75% moisture content (MD) group retained higher water-soluble carbohydrate, glucose, sucrose and fructose concents. The LP and CE inoculations significantly reduced the microbial community diversity, and lower values for the observed species, ACE, Chao1, and Shannon indices compared with CK-treated samples. Additives inhibited the growth of unfavourable bacteria (such as Clostridium) and increased the abundances of lactic acid bacteria (LAB); the maximum increases in the Lactiplantibacillus abundance were obtained in the LP- and CE+LP-treated samples, improving the microbial community structure in silage. In summary, adding LP and CE effectively improved the oat fermentation quality, and better performances in ensiling oat and lignocellulose degradation were obtained with LP and CE combinations, especially for the MD group of silages that were ensiled for 60 d. The addition of CE and LP at the appropriate moisture content might be helpful for producing high-quality oat silage, and also provide a simple and feasible method to enhance the effects of bacteria and enzymes.